Analysis of the Translation of Foreign Entity Financial Statements Based on PSAK 10 at PT Indofood CBP Sukses Makmur Tbk (ICBP) - Ali Hasan Mustofa; Mohamad Narandika; Viko Surya Pratama; Zidni ‘Ali; Endang Kartini Panggiarti; Erni Puji Astutik (Takaza Innovatix Labs Ltd., 2026)
Globalization drives Indonesian firms like PT Indofood CBP Sukses Makmur Tbk (ICBP) to expand abroad, requiring foreign entity financial statement translation for consolidated reporting in IDR, in line with PSAK 10 (IAS 21). This study aims to analyze ICBP's translation practices, exchange rate impacts on financials, and forex risk strategies using a descriptive qualitative case study on ICBP (population); sample from 2023-2024 consolidated statements and notes (secondary data), with documentation review, content/comparative analysis, and numerical simulations. Findings reveal ICBP translates assets/liabilities at closing rates, income at averages, equity at historical rates, routing differences to OCI (2024 gain Rp49 billion vs 2023 loss Rp540 billion); simulations confirm rate shifts affect equity and ratios, with overseas sales at 31% and natural hedging reducing negative reserves (Rp608 billion in 2024). In conclusion, ICBP complies effectively with standards and manages risks well, but should enhance disclosures and stress testing